Evaluation of a custom‐designed human–robot collaboration control system for dental implant robot. Issue 1 (8th November 2021) - Kan, Tian‐shu; Cheng, Kang‐jie; Liu, Yun‐feng; Wang, Russell; Zhu, Wei‐dong; Zhu, Fu‐dong; Jiang, Xian‐feng; Dong, Xing‐tao
Abstract: Background: The purpose of this study is to develop a methodology to better control a human–robot collaboration for robotic dental implant placement. We have designed a human–robot collaborative implant system (HRCDIS) which is based on a zero‐force hand‐guiding concept and a operational task management workflow that can achieve highly accurate and stable osteotomy drilling based on a surgeon's decision and robotic arm movements during implant surgery. Method: The HRCDIS brings forth the robot arm positions, exact drilling location, direction and performs automatic drilling. The HRCDIS can also avoid complex programing in the robot. The purpose of the study is to evaluate the accuracy of drilling resulting from our developed operational task management method (OTMM). The OTMM can enable the robot to switch, pause, and resume drilling tasks. The force required for hand‐guiding in a zero‐force control mode of the robot was detected by a 6D force sensor. We compared our force data to those provided by the manufacturer's manual. The study was conducted on a phantom head with a 3D‐printed jaw bone to verify the validity of our HRCDIS. We appraised the discrepancies between free‐hand drillings and the HRCDIS controlled drillings at apical centre and head centre of the implant and implant angulation to the baseline data from a virtual surgical planning model. Results: The average required force used by hand‐guiding to operate the robot with HRCDIS was near 7 Newton which is much less than the manufacturer's specification (30 Newton). The results from our study showed that the average error at implant head was 1.04 ± 0.37 mm, 1.56 ± 0.52 mm at the implant apex, and deviation of implant angle was 3.74 ± 0.67°. Conclusions: The results from this study validate the merit of the human–robot collaboration control by the HRCDIS. Based on the improved navigation system using HRCDIS, a robotic implant placement can provide seamless drilling with ease, efficiency and accuracy.